Characterization of Imagination Patterns in Students' Drawings Class 1 SDIT ALIF - Mulyani; Helmanto, Fachri; Rajagukguk, Zahra Fitrah (Mitra Palupi, 2025)
Background: Learning art plays an important role in developing students' creative and imaginative abilities. Through art, students not only learn about techniques and aesthetics but also express their ideas, feelings, and imagination. Art education is realized in the form of visual arts, which can be enjoyed through the sense of sight. This enhances local cultural awareness, fosters appreciation for cultural values, and serves as a medium for creativity development and the generation of new ideas. Art also enables self-actualization and the cultivation of creativity. Imagination, often referred to as the ability to visualize, is the capacity to form new images or sensations that are not directly experienced through sight, hearing, or other senses. Among elementary school students, drawing is one of the most dominant dimensions of imagination. Through drawing, students engage in activities such as scribbling, sketching, and coloring objects, which results in meaningful visual representations. Purpose: This article aims to explore the characterization of imaginative themes that emerge in drawings created by students. Design and methods: The method used in this study is the Narrative Method with a qualitative descriptive approach. The Narrative Method, as applied here, follows Polkinghorne's model. Narrative research aims to explore and understand individual experiences through storytelling. Polkinghorne’s model provides an analytical framework consisting of three key components: theme, context (domain), and cognitive structure. Data collection techniques used in this study include interviews and documentation. This research focuses on identifying the characterization of imaginative themes that appear in the drawings of first-grade students at SDIT ALIF. Results: The findings indicate that the principle of proximality is implemented by grouping nearby objects into patterns. This reflects a perceptual tendency wherein humans perceive closely positioned objects as part of a larger group or relationship. The principle of continuity suggests that individuals tend to view lines and patterns as unified or continuous entities. In the context of imagination, this means that people often form mental images of ideas or concepts in a continuous manner. For example, when imagining an object or scene, individuals tend to fill in the missing or unclear parts in their minds to create a completer and more coherent picture. Based on the discussion, the characterization of imaginative patterns in the drawings of first-grade students involves the senses of sight, hearing, touch, and taste.